Challenges in Automation by Public Relations Practitioners - Indriani Dewi Resky Ananda; Muhammad Akbar; Arianto Arianto (Borong Newinera Publisher, 2026)
This study aims to analyze the challenges faced by public relations practitioners in implementing automation in Makassar City. The study employed a descriptive qualitative approach involving public relations practitioners from Kalla Group, PT Pelabuhan Indonesia IV (Persero), and PT Vale Indonesia Tbk. Data were collected through in-depth interviews, observation, and documentation, and were analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. Data validity was strengthened through triangulation of interview, observation, and documentation data. The findings reveal four main challenges in public relations automation. First, internet speed and real-time communication demands require practitioners to respond rapidly while maintaining originality, accuracy, and credibility in organizational communication. Second, limited digital understanding and skills hinder the effective use of automation, artificial intelligence, and big data in public relations practices. Third, resistance to technological change occurs because automation is often perceived as a threat rather than a supporting tool. Fourth, ethical issues, data privacy concerns, and limited regulatory guidelines create uncertainty in the adoption of automation. These findings indicate that the successful implementation of public relations automation depends not only on technological availability but also on practitioner competence, organizational readiness, ethical awareness, and regulatory support. The study also confirms the relevance of Innovation Diffusion Theory in explaining the gradual adoption of automation in public relations practice.